Living and learning in the free school - Novak, Mark W. (Carleton library ;, 1975)
This volume is a pioneering study of a free school in an eastern Canadian city. The author describes the attempts of a small group of people to set up a school, bound in some ways to the conventional system, yet reaching beyond it with different ideals. One great value of the study is its careful description of the day-to-day activities as order and organization emerge from amorphous beginnings and develop in spite of threats from within and without. Further, the history of this specific free school is related to broader currents of North American life and to broader issues in social action and education.